ALK F1174V mutation confers sensitivity while ALK I1171 mutation confers resistance to alectinib. The importance of serial biopsy post progression. (January 2016) - Ou, Sai-Hong; Milliken, Jeffrey C.; Azada, Michele C.; Miller, Vincent A.; Ali, Siraj M.; Klempner, Samuel J.
Highlights: ALK F1174V sensitive to alectinib. ALK I1171S resistant to alectinib. Serial biopsy important. Abstract: Many acquired resistant mutations to the anaplastic lymphoma kinase ( ALK ) gene have been identified during treatment of ALK- rearranged non-small cell lung cancer (NSCLC) patients with crizotinib, ceritinib, and alectinib. These various acquired resistant ALK mutations confer differential sensitivities to various ALK inhibitors and may provide guidance on how to sequence the use of many of the second generation ALK inhibitors. We described a patient who developed an acquired ALK F1174V resistant mutation on progression from crizotinib that responded to alectinib for 18 months but then developed an acquired ALK I1171S mutation to alectinib. Both tumor samples had essentially the same genomic profile by comprehensive genomic profiling otherwise. This is the first patient report that demonstrates ALK F1174V mutation is sensitive to alectinib and further confirms missense acquired ALK I1171 mutation is resistant to alectinib. Sequential tumor re-biopsy for comprehensive genomic profiling (CGP) is important to appreciate the selective pressure during treatment with various ALK inhibitors underpinning the evolution of the disease course of ALK + NSCLC patients while on treatment with the various ALK inhibitors. This approach will likely help inform the optimal sequencing strategy as more ALK inhibitors become available. This case report also validates the importance of developing structurally distinct ALK inhibitors for clinical use to overcome non-cross resistant ALK mutations.